Enduring changes in brain metabolites and executive functioning in abstinent cocaine users. (1st September 2017) - Crocker, Candice E.; Purdon, Scot E.; Hanstock, Christopher C.; Lakusta, Bonnie; Seres, Peter; Tibbo, Philip G.
Graphical abstract: Highlights: Abstinent cocaine users show lasting changes in brain energy metabolism. Former users of crack cocaine show additional changes in brain glutamate levels. Performance on tasks of executive function correlated to NAA (neuronal energy). Abstract: Background: There is a paucity of data connecting the metabolic and cognitive functioning of abstinent cocaine users. This is a pressing public health concern as approximately 1% of the Canadian population and 0.4% of the global population is estimated to have used cocaine in the past year. Methods: Our clinical study compared the in vivo neurochemical profiles in the prefrontal cortex to cognitive tests associated with the same region in 21 moderate term abstinent cocaine users (average 187 days abstinent, range 15–1432 days), and 30 healthy controls using 3T 1 H MRS. Results: The abstinent cocaine users exhibited a 10% decrease in N -acetylaspartate (NAA) relative to healthy control subjects (p < 0.01, Cohen's d = 1.15). When subdivided by method of administration, a significant decrease in glutamate levels in former crack smokers compared to healthy controls (p < 0.05) was observed, this decrease was not present in powder users. Abstinent users were significantly worse than healthy controls on the Trail Making Test B (p < 0.05), and performance on this task was inversely related to NAA levels (p < 0.05). Abstinent cocaine users showed deficits in the Wisconsin card sorting test with failures to maintain set (p < 0.01). Conclusions: Our work suggests that there are subtle but important changes in the brain that remain even with the moderate term cessation of cocaine use.